Cardiotoxicity of environmental contaminant tributyltin involves myocyte oxidative stress and abnormal Ca(2+) handling - Pereira, C.L.V. (Environ Pollut, 2019)
Tributyltin (TBT) is an organotin environmental pollutant widely used as an agricultural and wood biocide and in antifouling paints. Countries began restricting TBT use in the 2000s, but their use continues in some agroindustrial processes. We studied the acute effect of TBT on cardiac function by analyzing myocardial contractility and Ca(2+) handling. Cardiac contractility was evaluated in isolated papillary muscle and whole heart upon TBT exposure. Isolated ventricular myocytes were used to measure calcium (Ca(2+)) transients, sarcoplasmic reticulum (SR) Ca(2+) content and SR Ca(2+) leak (as Ca(2+) sparks). Reactive oxygen species (ROS), as superoxide anion (O2(•−)) was detected at intracellular and mitochondrial myocardium. TBT depressed cardiac contractility and relaxation in papillary muscle and intact whole heart. TBT increased cytosolic, mitochondrial ROS production and decreased mitochondrial membrane potential. In isolated cardiomyocytes TBT decreased both Ca(2+) transients and SR Ca(2+) content and increased diastolic SR Ca(2+) leak. Decay of twitch and caffeine-induced Ca(2+) transients were slowed by the presence of TBT. Dantrolene prevented and Tiron limited the reduction in SR Ca(2+) content and transients. The environmental contaminant TBT causes cardiotoxicity within minutes, and may be considered hazardous to the mammalian heart. TBT acutely induced a negative inotropic effect in isolated papillary muscle and whole heart, increased arrhythmogenic SR Ca(2+) leak leading to reduced SR Ca(2+) content and reduced Ca(2+) transients. TBT-induced myocardial ROS production, may destabilize the SR Ca(2+) release channel RyR2 and reduce SR Ca(2+) pump activity as key factors in the TBT-induced negative inotropic and lusitropic effects.